Electronic Transport Properties in Bulk ZnO and Zn1-xMgxO Using Monte Carlo Simulation (Global Journal of Science Frontier Research, 2015)
In this paper, an investigation with the application of Monte Carlo simulations to steadystate electron transport and low-field electron mobility characteristics of in bulk ZnO in the wurtzite crystal structure and its alloy Zn 1-x Mg x O with different doping of Mg, x=0.05, 0.1 and 0.2. The Monte Carlo calculations are carried out using a three-valley model for the systems under consideration. The following scattering mechanisms, i.e, impurity, polar optical phonon and acoustic phonon are included in the calculation. The maximum electron drift velocity that is obtained at room temperature for 10 23 m -3 donor concentration is 1.97×10 7 cms -1 for ZnO in threshold field of 400 kV/cm. While the maximum electron drift velocity is 1.62×10 7 cms -1 , 1.03×10 7 cms -1 and 0.43×10 7 cms -1 for Zn 0.95 Mg 0.05 O, Zn 0.9 Mg 0.1 O and Zn 0.8 Mg 0.2 O in threshold field 700 kV/cm respectively. It can be seen the peak drift velocity for bulk ZnO is 1.97×10 7 cms -1 , while for Zn 1_x Mg x O the peak drift velocity decreases due to increasing electron effective mass.
Keywords: Electron Transport; Monte Carlo Simulation; Wurtzite Zn1-xMgxO; Effective Mass